Effects of Preharvest Methyl Jasmonate and Salicylic Acid Treatments on Growth, Quality, Volatile Components, and Antioxidant Systems of Chinese Chives - Wang, Cheng; Zhang, Jing; Xie, Jianming; Yu, Jihua; Li, Jing; Lv, Jian; Gao, Yanqiang; Niu, Tianhang; Patience, Bakpa Emily (Frontiers in Plant Science, 2022)
Methyl jasmonate (MeJA) and salicylic acid (SA) regulate the production of biologically active compounds in plants and stimulate the accumulation of plant aromatic substances. However, the underlying mechanisms of how MeJA and SA influence characteristic flavor compounds and the antioxidant activity of vegetables are poorly understood. Five MeJA and SA concentrations were used to investigate the dose-dependent effects of these phytohormones on the dry and fresh weight; chlorophyll abundance; the contents of vitamin C, soluble protein, and sugar, nitrate, total phenols, flavonoids, volatile components, and enzymatically produced pyruvic acid; and antioxidant activity in Chinese chive. We found that MeJA and SA at concentrations of 500 μM and 150 μM, respectively, significantly increased the levels of total chlorophyll, phenols and flavonoids, vitamin C, and volatile components and significantly reduced the accumulation of nitrate. In addition, compared with the control, 500 μM of MeJA significantly increased the soluble sugar and protein content, and 150 μM SA significantly increased the dry and fresh weight of Chinese chive. Furthermore, these concentrations of MeJA and SA significantly increased the enzymatic pyruvate content and the amount of sulfide and aromatic volatile compounds and improved the characteristic flavor compounds. The 2, 2-di-phenyl-1-picrylhydrazyl radical scavenging capacity, Trolox-equivalent antioxidant capacity, and ferric-reducing antioxidant capacity were significantly improved after a preharvest treatment with 500 μM MeJA and 150 μM SA, which could improve the antioxidant activity, thus improving the postharvest quality and preservation characteristics of Chinese chives. Taken together, a preharvest treatment with 500 μM MeJA and 150 μM SA is optimal to improve the growth, quality, antioxidant activity and flavor of Chinese chive, thereby enhancing its commercial value.